The Impact of HIIT on the cTnT Response in Sedentary Obese Young Men - Behroz Khodayari; Mohammad Reza Dehghan; Reza Nouri; Abbas Ali Gaeini; Mohammad Reza Kordi (Iranian Journal of Diabetes and Obesity, 2022)
Objective: Evaluation of the effect of 8 weeks of High-Intensity Interval Training (HIIT) on the serum level of cardiac troponin T (cTnT) in sedentary obese young men. Materials and Methods: Thirty sedentary men were randomly divided into 3 groups: the 30s HIIT training group (n=10), the 60s training group (n=10), and the control group (no exercise) (n=10). Interval training with 90 %VO2peak was done in 3 sessions for 8 weeks. cTnT was measured 5 times; pre-exercise, 4hrs, and 24hrs after the first session (4hF, 24hF), and 4hrs and 24hrs after the last training session (4hL, 24hL). ANOVA with repeated measures and Bonferroni post-hoc tests were used by SPSS 23 with a significance level of (P< 0.05). Results: The significant increase in serum levels of cTnT in the post-tests of the 60s HIIT compared to the first 24hrs and the last 24hrs (P= 0.0001). But in the 30s group it was not significant compared to the other measurements (P≥ 0/05). In the 2 training groups, serum levels of cTnT in the last 4hr post-tests of the last week were not significantly different from the 4hrs post-tests of the first week (P≥ 0.05). Conclusion: It seems that none of these activities cause heart damage sustained, and changes in cTnT levels in two 4hrs compared to the first and last 24hrs of the 60s group may be due to reversible leakage of cardiac cell membranes, and may continuous exercise will reduce this reduction.